Individual and household in-work poverty in Europe: understanding the role of labor market characteristics. Issue 1 (1st January 2019) - Filandri, Marianna; Struffolino, Emanuela
ABSTRACT: The article presents an analysis of the association between labor market characteristics related to female employment and the prevalence of in-work poverty. We compare two relative measures of in-work poverty: The individual definition refers to workers whose salary is below 60% of the median, while the household-level definition refers to individuals whose household income is below 60% of the median. Microdata from the 2014 EU-SILC survey and macrodata on involuntary part-time employment and female labor market participation are used to perform a multilevel analysis on 31 European countries. The results show a positive relationship between involuntary part-time work and in-work poverty according to the household definition. Female labor market participation is positively associated with the individual definition and negatively with the household one. However, after controlling for the level of within-country income inequality, only the effect of the female employment rate remains positive and significant for the individual in-work. These results shed light on the multifaceted role of labor market characteristics related to female employment and their implications for policy. We argue that the promotion of female participation should be combined with explicit measures to reduce the disadvantageous position of women in the labor market.